Agatha Christie's Miss Marple Volume 2 [videorecording (DVD)] : They do it with mirrors. A pocketful of rye. 4:50 from Paddington. The mirror crack'd from side to side. - Hickson, Joan, 1906-1998 (BBC Warner, 2015)
A collection of Miss Marple mysteries.